Risk of myocardial infarction and death in patients with atrial fibrillation treated with dabigatran or vitamin K antagonists - Darwiche, Walid; Bejan-Angoulvant, Theodora; Angoulvant, Denis; Babuty, Dominique; Fauchier, Laurent (Thrombosis and Haemostasis, 2016)
The safety of dabigatran versus adjusted-dose vitamin K antagonist (VKA) treatment is the subject of debate. We evaluated the risk of myocardial infarction (MI) or mortality in patients with atrial fibrillation (AF) treated in clinical practice with dabigatran or a VKA. We performed a meta-analysis of observational studies that included an adjusted or matched analysis and reported MI, or death in AF patients treated with dabigatran or a VKA. Ten published analyses met the inclusion criteria. Of the 539,559 patients, 17,365 (3%) patients were on dabigatran 110 mg twice daily (bid), 150,948 (28%) were on dabigatran 150 mg bid, and 371,246 (69%) were on VKA. Adjusted risk for MI versus VKA was 0.71 (0.47–1.07; p=0.10) in patients starting oral anticoagulant (OAC) treatment with dabigatran 110 mg, 0.82 (0.71–0.96; p=0.01) in patients starting dabigatran 150 mg, 1.40 (1.04–1.88; p=0.03) in patients switching OAC treatment to dabigatran 110 mg, and 1.28 (0.88–1.87; p=0.19) in patients switching OAC treatment to dabigatran 150 mg, with statistical homogeneity in each subgroup. Risk of death was consistently lower in patients treated with dabigatran 110 mg (HR 0.79; 0.65–0.96; p=0.02) or 150 mg (HR 0.65; 0.57–0.73; p<0.00001) versus VKA. In conclusion, dabigatran use, as currently prescribed in routine practice for AF patients, was associated with a lower risk of MI in OAC-naïve patients treated with dabigatran 150 mg compared with VKA, and a higher risk of MI in patients switching from VKA to dabigatran 110 mg. Risk of death was lower in AF patients treated with either dose of dabigatran versus VKA.
Keywords: Atrial fibrillation; dabigatran; myocardial infarction; vitamin K antagonist